Faktor Prediktor Yang Berpengaruh Terhadap Kunjungan Balita Di Posyandu Puskesmas Batua - Alam, Samsu; Haeruddin, Haeruddin; Rahmah, Nur; Baharuddin, Alfina (Window of Health : Jurnal Kesehatan, 2021)
Posyandu is one of the health services to make it easier for the community to find out or check health, especially mothers and children under five. Lack of parental knowledge about posyandu causes toddlers to not gain weight, experience malnutrition and experience dangerous diseases because they are not immunized. The type of research used is quantitative with a cross sectional study design. The sample in this study were all parents of toddlers who visited the Posyandu in the working area of ​​the Batua Health Center Makassar City who were willing to fill out the questionnaire. The number of samples in this study amounted to 95 people. Data were analyzed by simple regression test and logistic regression. The results showed that health promotion (p = 0.026), parental perception (p = 0.019) had an effect on toddler visits at the Batua Health Center in Makassar, while service quality (p = 0.949) had no effect on toddler visits at the Batua Health Center in Makassar. . The logistic regression value showed that the parent's perception variable had a more dominant effect on toddler visits with a value of (p=0.019 and exp value (B) 4.211). The conclusion of this study is that there is an influence between health promotion, parents' perceptions of toddler visits at the Posyandu at Batua Health Center Makassar City and there is no influence between service quality on toddler visits at the Posyandu Puskesmas Batua Makassar City. Suggestions to further researchers are to deepen this research by adding several variables or using qualitative methods. Keywords : Service Quality; Health Promotion; Parents' Perception.